Exploring the use of player load in elite soccer players - Oliva-Lozano, J. M.; Conte, D.; Fortes, V.; Muyor, J. M. (Sports Health: A Multidisciplinary Approach, 2023)
Background: The aims of this study were to (1) analyze the distribution of the player load (PLTOTAL) in 3 axes of movement (PLAP, anterior-posterior; PLML, medial-lateral; PLV, vertical) during elite soccer matches, (2) investigate the effect of playing position on PL-related variables, and (3) explore the association between PLTOTAL and distance covered by the players.